Systemic light-chain amyloidosis presenting with rapid progressive heart failure - MUTLU, BÜLENT; SARI, İBRAHİM; SÜNBÜL, MURAT (My University, 2013)
Systemic amyloid light-chain (AL) amyloidosis is caused by deposition of immunoglobulin light-chain proteins. AL amyloidosis is a rapidly progressive disease that affects multiple organs. Cardiac involvement is frequent (50%) and the median survival is 5 months following diagnosis. Although transthoracic echocardiography can show characteristics findings, further diagnostic modalities are required for diagnosis. The gold standard of the diagnosis is presence of the amyloid in a tissue biopsy specimen. We present here a case of AL amyloidosis with presenting rapid progressive heart failure. Despite improvements in diagnostic and therapeutic modalities, diagnosis is difficult and prognosis is still poor in patients with cardiac involvement as in the present case. © 2013, SAGE Publications. All rights reserved.
Keywords: heart failure; restrictive cardiomyopathy; systemic amyloidosis